How University Students as Non Native English Speakers Perform Face Threatening Acts - Ronald Maraden Parlindungan Silalahi (Universitas Bunda Mulia, 2018)
Politeness is necessary in any social interaction to avoid conflict which might arise because of the utterances. Politeness elaborates that we all have ‘face’ of wants and needs, when the wants and needs are not fulfilled properly, then a Face-Threatening Act (FTA) is executed (Lakoff, 1973). There are all sorts of Face-Threatening Acts, and sometimes the face threats are directed to the hearer, while in some other times they are aimed to the first speaker (Brown & Levinson, 1987). The students of Non-Native English Speaker (NNES) become the source data of this study. The way they perform the FTA based on circumstances, which are Power, Social Distance, and Imposition (Brown & Levinson, 1987). While performing FTA, the students have different ways of applying it in their daily lives. The greatest possibility is that the students might use politeness strategy to minimize FTA, by using negative politeness and positive politeness, which theory comes from Brown and Levinson (1987). Qualitative approach is used in this study, while the method is test analysis. The data is using Discourse Completion Test (DCT) of Politeness regarding various situations to perform FTA and it will be delivered to all University students. The result can be seen that most of the respondent's answers are identical to the expected answers from the data collectors. This proves that most of NNES are able to perform FTA appropriately, moreover when it is associated with politeness. The purpose of this study is to describe students’ comprehension, as well as to provide learning to who are not English native speakers, about FTA and ways that can be applied to perform FTA. It is expected that this study will help students to figure out about the function of FTA and understand more on how to perform FTA.Keywords: politeness, face threatening acts, non native English speakers, university students